Implementing a National Assessment of Educational Achievement - Greaney, Vincent; Kellaghan, Thomas (World Bank, 2012)
This third volume in the five-part National Assessments of Educational Achievement series, focuses on practical issues in the implementation of a national assessment. These include the representation of key educational stakeholders, required personnel and facilities, and the sequence of administrative activities in implementing an assessment. Particular attention is focused on sampling, such as defining the population to be assessed, elements of sampling theory, and the selection of schools and students to take part in an assessment. Readers are guided through the selection of a sample by working on a set of concrete tasks presented in the text, using data files in an accompanying CD. One section of Volume 3 is devoted to typical tasks involved in preparing, validating and managing data. Users are expected to develop competence in data preparation skills by carrying out the practical exercises in the CD. They are also shown how to complete important pre-analysis steps such as compute survey weights, calculate means and their sampling errors, and how to deal with non-responses and oversize and undersize schools. This volume is intended primarily for teams who are responsible for conducting national assessments and graduate students interested in technical aspects of large-scale surveys.